(untitled) (University Heart Journal, 2012)
Acute heart failure is a major health problem responsible for several million hospitalizations worldwide each year. Standard therapy has not changed for long time and includes diuretics and variable use of vasodilators or inotropes. Recently Nesiritide and Levosimendan are two drugs for the treatment of acute heart failure which have been approved by the Food and Drug Administration (FDA) and European Medicines Agency (EMEA), respectively. There was little concern that Nesiritide can worsen the renal failure but recent trials had abolished this concern. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10208 UHJ 2011; 7(1): 35-38